Mapping the Landscape of Transactions : The Governance of Business Relations in Latin America - Francis, David C.; Karalashvili, Nona; Murrell, Peter (World Bank, Washington, DC, 2018)
A new set of survey questions is used to map governance structures that firms employ to support the successful implementation of transactions. Responses to the questions were collected as part of the Enterprise Surveys in six South American countries. Without imposing any a priori model, latent class analysis (LCA) discovers meaningful patterns of governance structures that readily match constructs in the literature. All governance structures use bilateralism. Bilateralism and formal institutions are sometimes complements, but never substitutes. For each firm, LCA provides estimates of the posterior probability that the firm uses each of the discovered governance structures. These estimates can be used by researchers to go further, testing their own hypotheses relevant to Williamson's discriminating alignment agenda using additional data from the Enterprise Surveys or elsewhere. Variations in the effectiveness of different governance structures across countries and across different types of firms and transactions are explored. Regional variation within countries is greater than cross-country variation. Foreign-owned firms, exporters, larger firms, and better-managed ones are more likely to use governance structures that complement bilateralism with use of the legal system or with the help of paid third-parties.